2009
DOI: 10.1080/00207540802389227
|View full text |Cite
|
Sign up to set email alerts
|

Flexible manufacturing system selection using a combinatorial mathematics-based decision-making method

Abstract: A methodology based on a combinatorial mathematics-based decision-making method is proposed for evaluation of alternative flexible manufacturing systems. The methodology is developed to judge the relative merits of different flexible manufacturing systems for the industrial application considered. The proposed 'FMS selection index' evaluates and ranks flexible manufacturing systems for a given FMS selection problem. Two examples are included to illustrate the approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…The same FMS selection problem is now solved employing the six preference ranking methods and their relative ranking performance is shown in Table 23. From this table, it is found that there exists a perfect match between the rank ordering as obtained by ORESTE method and that derived by Rao and Parnichkun (2009). The Kendal's coefficient of concordance value is also estimated to be quite high (z = 0.9553) which indicates the existence of a near to perfect agreement between the considered methods.…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…The same FMS selection problem is now solved employing the six preference ranking methods and their relative ranking performance is shown in Table 23. From this table, it is found that there exists a perfect match between the rank ordering as obtained by ORESTE method and that derived by Rao and Parnichkun (2009). The Kendal's coefficient of concordance value is also estimated to be quite high (z = 0.9553) which indicates the existence of a near to perfect agreement between the considered methods.…”
Section: Resultsmentioning
confidence: 77%
“…A very high z value (z = 0.9778) assures the applicability of these preference ranking methods to solve this FMS selection problem too. From Tables 23 and 24, it becomes quite clear that ORESTE method provides the exact rank orderings of FMS alternatives when compared to those obtained by Rao and Parnichkun (2009). It can be concluded that ORESTE method outperforms the other methods with respect to their ranking performance.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…One may refer to Rao (2007) and Rao and Parnichkun (2009) for more details about how this scale is prepared.…”
Section: Fig 1 Linguistic Terms To Fuzzy Numbers Conversionmentioning
confidence: 99%